Dampak Psikologis terkait Relasi Individu Dewasa Awal yang Mengalami Perceraian Orang Tua - Habibatul Ainina; Primatia Yogi Wulandari (Buletin Riset Psikologi dan Kesehatan Mental, 2023)
The impact of divorce mostly affects the psychological aspects of children and continues to be felt into adulthood. The success of early-adult individuals in forming relationships to complete developmental tasks is influenced by their cognitions and attributions of romantic relationships that are formed based on perceptions of their parents' relationship. The researchers used the narrative review method to determine the psychological impact related to the relationship of early adult individuals who experienced parental divorce. Research has found that divorce has both positive and negative impacts on children's psychological conditions, affecting their success in establishing relationships to complete early adult developmental tasks related to intimacy vs isolation. It is very important to do further research regarding the dynamics and what factors that influence the success of forming relationships so that individuals with parental divorce experiences can optimally complete their developmental tasks.